جائحة كورونا وأثرها على درس التربية البدنية والرياضية من الجانب النفسي الإجتماعي - شريط, أسامة; حميدوش, خالد بن الوليد (institut d’éducation sportive et physique / Université de Mostaganem, 2021)
ملخص البحث: جاءت هذه الد ا رسة تحت عنوان أثر جائحة كورونا على درس التربية البدنية والرياضية 17 ( سنة ،بحيث - من الجانب النفسي والاجتماعي لدى تلاميذ الطور الثانوي ) 15 تمحورت اهداف هذا البحث في التعرف على اثر جائحة كورونا على درس التربية - البدنية والرياضية من الجانب النفسي والاجتماعي لدى تلاميذ الطور الثانوي ) 15 17 ( سنة ، وقد تم ان افت ا رض ان لجائحة كوروناأثر سلبي على درس التربية البدنية 17 ( سنة - والرياضية من الجانب النفسي والاجتماعي لدى تلاميذ الطور الثانوي ) 15 .وتمثلت عينة د ا رستنا في 18 تلميذ اختيارها كان بطريقة عشوائية، كما تم استنتاج ان لجائحة كورونا أثر سلبي على درس التربية البدنية والرياضية واثرت ايضا على 17 ( سنة .وفي الأخير - الجانب النفسي والاجتماعي لدى تلاميذ الطور الثانوي ) 15 نقترح الاهتمام بالجانب النفسي والاجتماعي لضرورة رفع الحماس والحافز والتفاعل لدى التلاميذ في حصة التربية البدنية والرياضية في الحالات العادية والاستثنائية خاصة كجائحة كورونا. Summary: This study came under the title of the impact of the Corona pandemic on the physical and sports education lesson from the psychological and social aspect among students of the secondary stage (15-17) years, so that the objectives of this research centered on identifying the impact of the Corona pandemic on the lesson of physical and sports education from the psychological and social aspect among students. The secondary phase (15-17) years, and it has been assumed that the Corona pandemic has a negative impact on the physical and sports education lesson from the psychological and social aspect among students of the secondary phase (15-17) years. The sample of our study consisted of 18 students whose choice was random, and it was also concluded that the Corona pandemic had a negative impact on the physical and sports education lesson and also affected the psychological and social aspect of secondary school students (15-17) years. Finally, we suggest paying attention to the psychological and social aspect of the need to raise Enthusiasm, motivation and interaction of students in the physical and sports education class in normal and exceptional cases, especially such as the Corona pandemic Résumé de la recherche: Cette étude s'est présentée sous le titre de l'impact de la pandémie de Corona sur le cours d'éducation physique et sportive du point de vue psychologique et social chez les élèves du secondaire (15-17 ans), de sorte que les objectifs de cette recherche se sont concentrés sur l'identification des impact de la pandémie de Corona sur l'enseignement de l'éducation physique et sportive du point de vue psychologique et social chez les élèves.La phase secondaire (15-17) ans, et il a été supposé que la pandémie de Corona a un impact négatif sur la santé physique et sportive leçon d'éducation sous l'aspect psychologique et social chez les élèves de la phase secondaire (15-17) ans. L'échantillon de notre étude était composé de 18 élèves don’t le choix était aléatoire, et il a également été conclu que la pandémie de Corona avait un impact négatif sur le cours d'éducation physique et sportive et affectait également l'aspect psychologique et social des élèves du secondaire (15-17 ) ans Enfin, nous suggérons de prêter attention à l'aspect psychologique et social de la nécessité d'augmenter l'enthousiasme, la motivation et l'interaction des élèves de la classe d'éducation physique et sportive dans des cas normaux et exceptionnels, notamment tels que la pandémie de Corona.
MEPS-2021-17
Keywords: الكلمات المفتاحية جائحة كورونا – درس التربية البدنية والرياضية – الجانب النفسي والاجتماعي